Empowerment Programs and Policies For People With Disabilities In Indonesia-Australia - Arni Surwanti; Meika Kurnia Puji Rahayu (International Journal of Science and Environment (IJSE), 2025)
One of the challenges for persons with disabilities is the low employment opportunities caused by the social stigma upon these people. Persons with disabilities can be discriminated against socially, culturally, and in terms of facilities both within their families, communities, and in society at large. Empowerment programs can support the employment of persons with disabilities. Policies to promote such programs are introduced both in middle-income countries, such as Indonesia, and high-income countries, such as Australia. This study analyzes the historical development of policies to promote economic empowerment programs for persons with disabilities in Indonesia and Australia. It uses a strength-based approach to help identify the factors that support and those that hinder the successful implementation of the programs in these two countries. The results will contribute recommendations to the government and relevant stakeholders in developing initiatives and policies to improve economic empowerment programs for persons with disabilities in Indonesia.